Finite element analysis of propagating waves in non-destructive testing for defects characterisation in pipes - Mohamad Yusoff, Mohd Shahrul Azmi (2017)
Early detection of defects in commercial piping system is important in preventing enormous and expensive repair due to large unprecedented failure caused by corrosion, blockage or structural deformation. Over the years, various non-destructive inspection methods were used within the multimillion oil and gas industry to prevent losses of both human and money. Most of the research has been done within the solid isotropic media by mean of studying the ultrasonic guided test. The dispersive nature of propagation within solid media requires great experience from technicians in interpreting the signals acquired through the available sensors. There is an inevitable need for industry to interpret the signal easier with available artificial intelligent techniques; however this would require more data for training. In this research, the time domain reflectometry will be investigated for various acoustic wave reflections from defects within a pipeline system by means of 3-dimensional finite element modelling and experimental procedures. Artificial defects of different sizes will also be modelled to understand the propagation of acoustic wave within the pipe. An incident wave will be introduced at a point along the pipe and the travelling path of longitudinal wave within the pipe will be studied. The potential implementation of local mesh refinement in commercially available FE packages is considered and discussed in the context of the choices open to the modellers. The outcome of the techniques and information will be a significant improvement in FE modelling of acoustic wave in non-isotropic media. This method will be the potential solution to the current prediction method used in Support Vector Machine by simply reducing the needs to have physical experimental data of defects. Modelling of various defects and failures can be done with the method presented in this thesis, as an input to a greater work within non-destructive testing in pipe. In the experiment, we have validated the predicted results of Finite Element Analysis to the defects responses, confirming to the hypothesis of this research.